A Study of Possible Associations Between Single Nucleotide Polymorphisms in the Estrogen Receptor 2 Gene and Female Sexual Desire. (10th November 2014) - Gunst, Annika; Jern, Patrick; Westberg, Lars; Johansson, Ada; Salo, Benny; Burri, Andrea; Spector, Tim; Eriksson, Elias; Sandnabba, N. Kenneth; Santtila, Pekka
Abstract Introduction Female sexual desire and arousal problems have been shown to have a heritable component of moderate size. Previous molecular genetic studies on sexual desire have mainly focused on genes associated with neurotransmitters such as dopamine and serotonin. Nevertheless, there is reason to believe that hormones with more specific functions concerning sexuality could have an impact on sexual desire and arousal. Aim The aim of the present study was to investigate the possible effects of 17 single nucleotide polymorphisms (SNPs) located in estrogen receptor genes on female sexual desire and subjective and genital arousal (lubrication). Based on previous research, we hypothesized that ESR1 and ESR2 are relevant genes that contribute to female sexual desire and arousal. Main Outcome Measures The desire, arousal, and lubrication subdomains of the Female Sexual Function Index self‐report questionnaire were used. Methods The present study involved 2, 448 female twins and their sisters aged 18–49 who had submitted saliva samples for genotyping. The participants were a subset from a large‐scale, population‐based sample. Results We found nominally significant main effects on sexual desire for three ESR2‐linked SNPs when controlled for anxiety, suggesting that individuals homozygous for the G allele of the rs1271572 SNP, and the A allele of the rs4986938 and rs928554 SNPs had lower levels of sexual desire. The rs4986938 SNP also had a nominally significant effect on lubrication. No effects for any of the SNPs on subjective arousal could be detected. Conclusions The number of nominally significant results for SNPs in the ESR2 gene before correcting for multiple testing suggests that further studies on the possible influence of this gene on interindividual variation in female sexual functioning are warranted. In contrast, no support for an involvement of ESR1 was obtained. Our results should be interpreted with caution until replicated in independent, large samples. Gunst A, Jern P, Westberg L, Johansson A, Salo B, Burri A, Spector T, Eriksson E, Sandnabba NK, and Santtila P. A study of possible associations between single nucleotide polymorphisms in the estrogen receptor 2 gene and female sexual desire. J Sex Med 2015;12:676–684.